Pemikiran John Locke Tentang Pendidikan - Akbar, Muhammad Ravi (Jurnal Ilmiah Guru Madrasah, 2023)
John Locke's thoughts about education have become an important subject in the study of education. The background of the problem shows the complexity of society's demands during Locke's time and how his thinking tried to answer the educational challenges of his time. This research aims to detail Locke's educational concepts, analyze their philosophical foundations, and evaluate their impact on the development of the education system. The research method involves an intensive literature review of Locke's original works and expert interpretations. The research results outline Locke's views on the role of experience and the origins of knowledge in the formation of individual character. In addition, this research discusses the concept of human rights in the educational context advocated by Locke, revealing its relevance to the development of the modern education system. The conclusion highlights Locke's valuable contribution in establishing an educational paradigm that emphasizes the development of natural human potential and the formation of rational citizens Abstrak Pemikiran John Locke tentang pendidikan telah menjadi subjek penting dalam kajian ilmu pendidikan. Latar belakang masalah mengemukakan kompleksitas tuntutan masyarakat pada masa Locke dan bagaimana pemikirannya berusaha menjawab tantangan pendidikan pada zamannya. Penelitian ini bertujuan untuk merinci konsep-konsep pendidikan Locke, menganalisis landasan filosofisnya, serta mengevaluasi dampaknya terhadap perkembangan sistem pendidikan. Metode penelitian melibatkan telaah pustaka intensif terhadap karya-karya asli Locke dan interpretasi para ahli. Hasil penelitian menguraikan pandangan Locke tentang peran pengalaman dan asal-usul pengetahuan dalam pembentukan karakter individu. Selain itu, penelitian ini membahas konsep hak asasi manusia dalam konteks pendidikan yang diadvokasi oleh Locke, mengungkapkan relevansinya dengan perkembangan sistem pendidikan modern. Kesimpulan menyoroti kontribusi berharga Locke dalam membentuk paradigma pendidikan yang menekankan pada pengembangan potensi alami manusia dan pembentukan warga negara yang berakal budi